Fistula formation between infected pelvic lymphocele and sigmoid colon: A rare complication of pelvic lymphadenectomy - Allioui, Soukaina (Radiol Case Rep, 2021)
Lymphocele formation following pelvic lymphadenectomy is a well-known complication. In this article, we report a 56 years old female patient with a pelvic infected lymphocele fistulised in the sigmoid discovered in imaging 2 months after pelvic surgery. Lymphocele complications are rare and their diagnosis is based on imaging. However, lymphocele as a potential cause for fistula in the bowel as a particular new case has not been found in literature search.